Nomenclatural consequences of some new combinations and replacement names in Eulophia (Orchidaceae: Eulophiinae) - Bhattacharjee , A.; Bandyopadhyay , S.; Chakraborty, K.; Sardar , S.; Mondal , S.; Chakraborty , S.; Sarkar, S. (Rheedea, 2026)
The nomenclatural consequences of some recently published new combinations and replacement names under Eulophia R.Br. (Orchidaceae) are discussed with a suggestion to follow the existing usage of these name under Geodorum Andrews until their nomenclatural status is resolved in the future.